Role of hypothetical protein PA1-LRP in antibacterial activity of endolysin from a new Pantoea phage PA1 - Tian, Ye; Xu, Xinyan; Ijaz, Munazza; Shen, Ying; Shahid, Muhammad Shafiq; Ahmed, Temoor; Ali, Hayssam M.; Yan, Chengqi; Gu, Chunyan; Lu, Jianfei; Wang, Yanli; Ondrasek, Gabrijel; et al. (Frontiers in microbiology, 2024)
has emerged as a significant plant pathogen affecting various crops worldwide, causing substantial economic losses. Bacteriophages and their endolysins offer promising alternatives for controlling bacterial infections, addressing the growing concerns of antibiotic resistance. This study isolated and characterized the phage PA1 and investigated the role of PA1-LRP in directly damaging bacteria and assisting endolysin PA1-Lys in cell lysis, comparing its effect to exogenous transmembrane domains following the identification and analysis of the PA1-Lys and the PA1-LRP based on whole genome analysis of phage PA1. Additionally, this study also explored how hydrophobic region of PA1-LRP (HPP) contributes to bacterial killing when combined with PA1-Lys and examined the stability and lytic spectrum of PA1-Lys under various conditions. Phage PA1 belonging to the family exhibited a broad host range against strains, with a latent period of 40 minutes and a burst size of 17.17 phages per infected cell. PA1-Lys remained stable at pH 6-10 and temperatures of 20-50°C and showed lytic activity against various Gram-negative bacteria, while PA1-Lys alone could not directly lyse bacteria, its lytic activity was enhanced in the presence of EDTA. Surprisingly, PA1-LRP inhibited bacterial growth when expressed alone. After 24 h of incubation, the OD value of pET28a-LRP decreased by 0.164 compared to pET28a. Furthermore, the lytic effect of co-expressed PA1-LRP and PA1-Lys was significantly stronger than each separately. After 24 h of incubation, compared to pET28a-LRP, the OD value of pET28a-Lys-LRP decreased by 0.444, while the OD value increased by 3.121. Live/dead cell staining, and flow cytometry experiments showed that the fusion expression of PA1-LRP and PA1-Lys resulted in 41.29% cell death, with bacterial morphology changing from rod-shaped to filamentous. Notably, PA1-LRP provided stronger support for endolysin-mediated cell lysis than exogenous transmembrane domains. Additionally, our results demonstrated that the HPP fused with PA1-Lys, led to 40.60% cell death, with bacteria changing from rod-shaped to spherical and exhibiting vacuolation. Taken together, this study provides insights into the lysis mechanisms of phages and identifies a novel lysis-related protein, PA1-LRP, which could have potential applications in phage therapy and bacterial disease control.